The Sensory Evaluation of Traditional Indonesian Braised Broiler Thigh Meat ‘Ungkep’ With Different Concentrations of Indigenous Herbs and Spices - Prasetyo, Budi; Prayitno, Agus Hadi; Siswantoro, Dharwin; Asri, Dewi; Putra, Yoga Dwi Kurnia; Agustin, Melda Nur; Ramadhanti, Faradziba Rahayu Sifa’ Iftitah (International Journal of Technology, Food and Agriculture, 2024)
This study aimed to explore the impact of varying concentrations of indigenous herbs and spices on the sensory evaluation of braised broiler thigh meat “ayam ungkep”. The research materials included broiler thigh meat, garlic, shallots, turmeric, ginger, candlenut, sugar, galangal, coriander, salt, palm oil, and monosodium glutamate. The treatment concentrations for broiler thigh meat were set at 20%, 25%, and 30% of the meat's weight. A hedonic test of cooked broiler thigh meat was performed as part of the sensory evaluation by 40 panelists who were not instructed. The hedonic test evaluated color, flavor, texture, tenderness, juiciness, and overall acceptability among other parameters. The non-parametric Hedonic Kruskal-Wallis test was used to assess the sensory evaluation data. After determining whether there was a significant difference (P<0.05), Duncan's New Multiple Range Test was performed. The findings showed that the color, flavor, texture, tenderness, juiciness, and overall acceptability of braised broiler thigh meat were not significantly affected by different levels of indigenous herbs and spices. For more effective produce of the still-preferred traditional Indonesian braised chicken meat products, it was suggested that the concentration of indigenous herbs and spices in broiler meat processing remain at 20% because, with this concentration, the panellists still like the resulting braised chicken.